Pengembangan Media Pembelajaran Berbasis Proyek Melalui Aplikasi Canva Terhadap Kreatifitas Mahasiswa Biologi IAIN Ternate - Isran Sahil (Jurnal Ilmiah Wahana Pendidikan, 2023)
Develompment of project-based learning media through the canva application to the creativity of biologi students at IAIN Ternate. The covid-19 pandemic made a study at home policy so that several regions in eastern Indonesia, one of which was north Maluku utara province, had many obstacles to learling at home. This study aims to see the presentation of IAIN Ternate Tadris Biology Students using well developed information technology. This study uses the ADDIE model that is: Analysis, design, development, implementation and evaluation. This sample of population is biology studenst in semester five with a total of eight studenst